PENGARUH INDEPENDENSI KOMPETENSI DAN ETIKA AUDITOR TERHADAP KINERJA AUDITOR INTERNAL (Studi Kasus Pada Inspektorat Kabupaten Cirebon) - Halimah Nur Hotimah (PT Naureen Digital Education, 2023)
This study aims to find out: (1) The effect of auditor independence on auditor performance, (2) The effect of auditor competence on auditor performance, (3) The influence of auditor ethics on auditor performance. The research approach used in this study is a quantitative approach., the type of data used is primary data by distributing questionnaires to respondents then analyzed using descriptive statistical methods, validity tests, reliability tests, spearman rank correlation analysis and rank correlation significance tests. From the results of the analysis, it can be concluded that: 1. There is a close relationship, positive influence, and significant independence of auditors on the performance of auditors at the Cirebon Regency Inspectorate, 2. There is a close relationship, positive influence, and significant auditor competence on auditor performance at the Cirebon Regency Inspectorate, 3. There is a close relationship, positive influence, and significant auditor ethics on auditor performance at the Cirebon Regency Inspectorate.